Determinants of smallholder teff farmer’s chemical fertilizer technology adoption in Southern Ethiopia, in case of Gena District in Dawro Zone (Heckman Two-Stage Model) - Deresse Dalango; Tekilu Tadesse (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2019)
Increasing technology adoption among smallholder farmers has a big potential to uplift living standards of poor through increasing production and consumption pattern. The objective of this study was analyzing determinant of smallholder teff farmer’s chemical fertilizer technology adoption and its intensification in Southern Ethiopia, in case of Gena district in Dawro Zone. The study used data from 180 respondents from four selected teff dominant kebeles of Gena districts in Dawro Zone, through structured questioner. The descriptive statistics and Heckman two stage econometric methods were employed to analyze data collected from sampled household. The significance of coefficient of inverse Mill’s ratio ( ) indicates the presence of selection bias and the effectiveness of applying Heckman two stage model. In the 1st stage of probit regression results of study show that the adoption decision of chemical fertilizer use were driven by factors such as farm size, size of family, family labor, education, access to credit; access to information, distance to near market place. In the second stage, the intensification of chemical fertilizer application was influenced by membership to cooperative, availability of extension service, access to credit, size of farm land, size of family member, family labor, educational status, sex of head. The policies which expand the accessibility of credit service, dissemination of productive agricultural technology information, and creating opportunity of education for farm house hold has potential to increase the chance of chemical fertilizer adoption decision and strengthen the level of adoption among smallholder farmers.